Review of Chapter 4, “Joseph Ratzinger and the Jews.” Karma Ben-Johanan’s "Jacob’s Younger Brother: Christian-Jewish Relations after Vatican II" - Anton, Emil (Studies in Christian-Jewish Relations, 2023)
No abstract is available.